2011
DOI: 10.3851/imp1913
|View full text |Cite
|
Sign up to set email alerts
|

Il28B Cc-Genotype Association with Hla-Dqb1*0301 Allele Increases the Prediction of Spontaneous HCV RNA Clearance in Thalassaemic HCV-Infected Patients

Abstract: In addition to IL28B CC-genotype, HLA DQB1*0301 helps in predicting natural clearance of HCV after acute infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Thus, our results corroborate the fact that favorable alleles at both rs12979860 and rs8099917 loci and low age group are two significant factors that strongly contribute to the spontaneous clearance of the virus from the host system than without spontaneous clearance individuals (p < 0.05; Table ). Our data are also in accordance with the reports published elsewhere, which show that carriers of the favorable genotypes at rs12979860 and rs8099917 have a higher rate of spontaneous clearance of HCV during the acute phase of the infection …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our results corroborate the fact that favorable alleles at both rs12979860 and rs8099917 loci and low age group are two significant factors that strongly contribute to the spontaneous clearance of the virus from the host system than without spontaneous clearance individuals (p < 0.05; Table ). Our data are also in accordance with the reports published elsewhere, which show that carriers of the favorable genotypes at rs12979860 and rs8099917 have a higher rate of spontaneous clearance of HCV during the acute phase of the infection …”
Section: Discussionsupporting
confidence: 93%
“…However, none of the previous studies have typically focused on any particular HCV‐infected high‐risk population group. Studies conducted by different groups explored the role of IL28B SNPs in thalassemia but their sample size was small and showed no correlation between HCV infection and serum ferritin load. To the best of our knowledge this is the first comprehensive study to find the role of IL28B at loci rs12979860 and rs8099917 in patients with thalassemia with or without HCV standard therapy in India.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is no association between DQB1*0201 and persistence of infection ( P =.39); this may be due to inadequate sample size to detect this genetic susceptibility in this special group of patients. The absence of HCV genotypic determination in most of the studied group may have confounded the analysis . One study on an ethnically complex Brazilian population found that DQB1*03 was associated with the SVC, while another from south‐east Brazil found that the frequency of DQB1*03 was lower among infected individuals than in the control group, but this was inconclusive due to the absence of the SVC group .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of HCV genotypic determination in most of the studied group may have confounded the analysis. 38 One study on an ethnically complex Brazilian population found that DQB1*03 was associated with the SVC, 39 while another from south-east Brazil found that the frequency of DQB1*03 was lower among infected individuals than in the control group, but this was inconclusive due to the absence of the SVC group. 40 In a Japanese population, it was found that the frequency of DQB1*0301 allele was higher in patients with the asymptomatic carrier state than in those T A B L E 4 Odds ratio of common alleles of DQB1 locus in different study groups with liver cirrhosis.…”
Section: Hla-dqb1 Polymorphisms and Hcv Infection Outcome Inmentioning
confidence: 99%
“…The difference in resolution rates among the different genotype combinations was highly significant and suggests that the effect of IkBε is not redundant in the presence of the IL28B effect. Other studies have shown improved predictive value for spontaneous or treatment‐induced viral resolution of the IL28B genotypes when combining them with human leucocyte antigen and killer‐cell immunoglobulin‐like receptor genotypes . This shows the value of combining genetic factors in a predictive model and thereby improving the clinical management of HCV‐infected individuals.…”
Section: Discussionmentioning
confidence: 87%